The effect of hand splints on stereotypic hand behavior in Rett's syndrome - Bumin, Gonca; Uyanık, Mine; Kayıhan, Hülya; Düger, Tülin; Topçu, Meral (The Turkish Journal of Pediatrics, 2002)
The purpose of this study was to examine the effect of hand splints and one elbow restraint on persistent stereotypic hand movements of four girls with Rett's syndrome.Among the most characteristic features of Rett's syndrome are stereotypic hand wringing and loss of previously acquired functional hand skills. Hand splints and one elbow restraint were used in this study. The subject's stereotypic hand behavior and functional hand use were calculated from five-minute segmental video tape recordings. The study consisted of three phases: baseline, intervention, and withdrawal.All subjects demonstrated a decrease in stereotypic hand behavior after the application of hand splints. Although splints showed a positive effect on hand movements in Rett's syndrome, they could also lead to other, undesirable, movements. Whether splints have a positive effect on the functional use of the hand should be investigated in more subjects.
Keywords: Rett's syndrome; stereotypic movements; hand splints